Youth representation in the European Parliament: The limited effect of political party characteristics - Aksel Sundström; Daniel Stockemer (Intergenerational Justice Review)
Which party characteristics contribute to the representation of young legislators? We examine this question quantitatively, focusing on the European Parliament (EP), and gauge the influence of the age of the party leader, the age of the party, the size of its support, party ideology and party nomination procedures on the age of politicians, based on data of all members who have served in the EP. We find that none of these characteristics matter substantively in explaining young representatives’ presence and discuss ways to further the field of research on youth representation.